42. Muscle ultrasound as a further tool in diaphragmatic muscle evaluation in Amyotrophic Lateral Sclerosis. Issue 12 (December 2016) - Sartucci, F.; Bocci, T.; Di Rollo, A.; Barloscio, D.; Parenti, L.; Santin, M.; Rossi, B.; Dolciotti, C.; Cavalli, L.; Pelagatti, A.; Bongioanni, P.; Del Gamba, C.
Abstract : Respiratory failure is an unavoidable stage in patients with Amyotrophic Lateral Sclerosis (ALS). Generally, diaphragmatic function is investigated by electromyography of the diaphragm muscle (DM) and electroneurography of the phrenic nerve. In our study we evaluated the usefulness of ultrasonography for morphological (thickness and echogenicity) and functional (changes during the respiratory dynamics) assessment of DM, correlating these findings with respiratory function and disease severity scores, in order to underline if this approach can replace the current diagnostic methods. We assessed 11 ALS patients (9 m e 2 f, mean age: 63.9 + 9.5 yy) and 11 healthy subjects, age- and gender-matched, using a Telemed Echo-wave II ultrasound. Mean DM thickness at rest (2.18 vs 3.45 mm), as well as thickness variations during breathing (0.4 vs 1.16 mm) were reduced in all patients, or abolished in 3 severe cases. Occasionally fasciculations were noticed, rarely fibrillation. Those findings did not correlate with forced vital capacity, maximum inspiratory and expiratory pressure. Ultrasound of DM resulted as an easy and rapid tool, devoid of discomfort and risks for ALS patients and able to provide further informations to assess and predict respiratory failure severity, allowing to plan therapeutic strategies.